Internasionalisasi Pendidikan dan Strategi Pengembangan Mutu Perguruan Tinggi Agama Islam di Indonesia: Sketsa Edukatif Manajemen Mutu - M Thoyib (EL-TARBAWI, 2008)
Internationalization is truly acceleration into all fields that able topierce the limit of field and regional otorities of a state, or on Robertson’sview (2003), internationalization is the third wave of globalization, thatable to accompany a state becoming superior or on the contrary, will befalling out. The existence and success of higher education especially forIslamic Higher Education in Indonesia (PTAI) in the globalization eraand liberalization of education in the future will be decided so much bythe seatle of akademic and educational infrastructures preparation ofthe higher education and has more farther at international competitionlevel without lossing Islamic morality character as its basic application.This assumtion also has to be supported by more better strategies fordeveloping quality system of Islamic higher education; first, managementof higher education at Islamic higher education (PTAI) should beable to concentrate for international academic quality development.Strengthening its management should be supported by; (1) implementation of acreditation for regional and international scales, (2) otonomy of organizing higher education that more established with empowering local and national potentialities, (3) accuntability of Islamic higher education aplication supported by the whole stakeholders, and (4) competencies of infrastructures and human resources at Islamic higher education is always improved through resources improvement policy. Second, aplication of quality management should be supported by good academic atmosphere implemented on the whole stakeholder’s commitment for achieving more better quality of Islamic higher education in the next future. Third, humanistic sense of diversity has to becoming primary supporting tool for Islamic higher education to face internationalization application more humanistic and large international academic networking for supporting Indonesia’s human resources becoming qualified, productive, innovative and competitive in all competition scales.